ANALISIS PENENTUAN HARGA POKOK USAHA TANI BERAS PADA KECAMATAN WALANTAKA KOTA SERANG - kiki Roidelindho; Dian Puspita Novrianti; Samsu Hilal; Nezly Nurlia Putri (Universitas Putera Batam, 2022)
In industry, especially the agricultural industry, in producing products that will be sold to consumers, one of the important aspects of conducting agricultural business, especially rice cultivation, must pay attention to the basic price. Determination of the cost of goods is intended to minimize losses that can occur. To obtain the basic price of rice farming, calculations are made of crop production, costs of fertilizers and medicines, tax expenses, capital interest, equipment depreciation, labor costs, transportation costs. In this study the method used was purposive sampling with the consideration that the largest rice producing area was in the Walantaka sub-district. The data was taken from farmers in 3 sub-districts, namely Nyapah, Tegal Sari and Lebakwangi sub-districts. The results of the study showed that the costs incurred for rice farming were Rp. 6,223,500 (Nyapah), Rp. 5,993,500 (Tegal Sari), Rp. 5,930,000 (Lebak Wangi). The basic price of rice farming results was obtained at Lebakwangi Rp. 6,760.00, Tegal sari Rp. 6,117.00 and Nyapah Rp. 5,331.00 based on explicit and implicit cost calculations. For the basic price based on explicit costs, the price obtained is Rp. 4,576 (Nyapah), Tegal Sari is Rp. 5,257, Lebakwangi is Rp. 5,813 . Keywords: Rice farming, production costs, basic prices